The benefits of shared leadership on minister-junior minister delegation and accountability - Silveira, Pedro (Frontiers in Political Science, 2024)
The relationships between ministers and their junior ministers have hardly been addressed in the literature, yet they are crucial to understanding government departmental dynamics. Using a principal agent framework, this article analyses 144 minister-junior minister relationships in three Portuguese governments (2005–2015), uncovering serious divergences (agency losses). The results were obtained through a qualitative approach, using many sources, including 111 interviews with former Portuguese prime ministers, ministers and junior ministers, content analysis, and one Minister's direct observation. It concludes that sharing the decisional power (shared leadership) improves accountability (promoting preference alignment and reducing asymmetric information), preventing and dealing effectively with divergences.